Screening of a Focused Ubiquitin-Proteasome Pathway Inhibitor Library Identifies Small Molecules as Novel Modulators of Botulinum Neurotoxin Type A Toxicity - Sen, Edanur; Kota, Krishna P.; Panchal, Rekha G.; Bavari, Sina; Kiris, Erkan (Frontiers in Pharmacology, 2021)
Botulinum neurotoxins (BoNTs) are known as the most potent bacterial toxins, which can cause potentially deadly disease botulism. BoNT Serotype A (BoNT/A) is the most studied serotype as it is responsible for most human botulism cases, and its formulations are extensively utilized in clinics for therapeutic and cosmetic applications. BoNT/A has the longest-lasting effect in neurons compared to other serotypes, and there has been high interest in understanding how BoNT/A manages to escape protein degradation machinery in neurons for months. Recent work demonstrated that an E3 ligase, HECTD2, leads to efficient ubiquitination of the BoNT/A Light Chain (A/LC); however, the dominant activity of a deubiquitinase (DUB), VCIP135, inhibits the degradation of the enzymatic component. Another DUB, USP9X, was also identified as a potential indirect contributor to A/LC degradation. In this study, we screened a focused ubiquitin-proteasome pathway inhibitor library, including VCIP135 and USP9X inhibitors, and identified ten potential lead compounds affecting BoNT/A mediated SNAP-25 cleavage in neurons in pre-intoxication conditions. We then tested the dose-dependent effects of the compounds and their potential toxic effects in cells. A subset of the lead compounds demonstrated efficacy on the stability and ubiquitination of A/LC in cells. Three of the compounds, WP1130 (degrasyn), PR-619, and Celastrol, further demonstrated efficacy against BoNT/A holotoxin in an in vitro post-intoxication model. Excitingly, PR-619 and WP1130 are known inhibitors of VCIP135 and USP9X, respectively. Modulation of BoNT turnover in cells by small molecules can potentially lead to the development of effective countermeasures against botulism.